Geomorphological, hydrographical and sedimentological processes at the Serres basin due to quaternary fault tectonics - ΨΙΛΟΒΙΚΟΣ, Α.; ΒΑΒΛΙΑΚΗΣ, Ε.; ΒΟΥΒΑΛΙΔΗΣ, Κ.; ΠΑΠΑΦΙΛΙΠΠΟΥ-ΠΕΝΝΟΥ, Ε. (Bulletin of the Geological Society of Greece, 2001)
On the S W foothills of Mt. Menikion and the NE part of Serres basin, four zones of composite alluvial fans have been formed. The upper zone of thick hard fanglomerates lies at altitudes of 280 to 600 m on Mt. Menikion schists and marbles. The high zone of loose fanglomerates, with red-brown sand matrix, lies at altitudes of 200 to 350 m on the neogene deposits. The intermediate zone of mixed coarse and fine elastics lies at altitudes of 80 to 140 m on neogene deposits. The lower zone of gravel, sand and silt deposits lies at altitudes of 10 to 60 m on quaternary terrace deposits. Each zone is approximately 13 - 17 km long and 1-2 km wide, with E/SE - W/NW trend, almost parallel to the main fault lines of the area. The fan zones were deposited along the slopes of Mt. Menikion and Serres basin, owing to the fault tectonics of the area. Several E/SE - W/NW trending parallel to each other listric faults, were formed on the basement on Mt. Menikion and the neogene deposits of Serres basin. Their blocks slided and turned downstream along the faults, so that their surface inclined backwards. Close to the faults, parallel valleys were formed. They filled up with quaternary deposits, brought down by activated torrents. The torrents flowed transversely to the fault blocks. At the inner parts of the blocks they deposited clastic material in the form of alluvial fans. In the outer – higher part of the blocks they were incised in the rocks or the neogene sediments, to form narrow valleys, with terraces along their walls. The staircase development of the relief finally resulted in a staircase development of the fan zones. The two zones, upper and high, seem to be Pleistocene in age and the torrents have already incised in the fan material. The two zones, intermediate and lower, seem to be Holocene in age and are still active. Tectonic activity seems to have been the main cause of sediment entrapment in the Serres basin and the low sediment delivery rate of the river Strymon during the Quaternary.